Peran Pengguna Game Online pada Aspek Pendidikan Lintas Budaya dalam Meningkatkan Toleransi di Platform Game Online - Padli, Sul; Najamuddin, Najamuddin; Alwi, Alimin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to examine the role of online game players in building intercultural tolerance through interactions in cyberspace. This study uses a qualitative approach with a phenomenological study type to explore the experiences of online game players in cross-cultural interactions. The research subjects consisted of seven players selected through purposive sampling, using snowball sampling until the data was saturated. Data collection techniques were through semi-structured interviews and participant observation, then data analysis used the interactive model of Miles and Huberman through the stages of reduction, presentation, and drawing conclusions. Data validity was ensured through triangulation of sources and methods, accompanied by member checking with participants. The results of the analysis show four main findings: (1) online games act as a means of social interaction as well as entertainment, (2) cross-cultural communication is a factor that can strengthen and hinder relationships, (3) the practice of tolerance is reflected in the ability to manage emotions, compromise, act as a mediator, and use humor, and (4) educational values are apparent in the form of increased language skills, empathy, patience, and appreciation for diversity. Although verbal and strategic conflicts often arise, the emerging resolution patterns show that digital space has strong potential as a medium for learning tolerance and cross-cultural collaboration.